2006
DOI: 10.1007/s10584-006-9106-6
|View full text |Cite
|
Sign up to set email alerts
|

Climate Risks and Their Impact on Agriculture and Forests in Switzerland

Abstract: There is growing evidence that, as a result of global climate change, some of the most severe weather events could become more frequent in Europe over the next 50 to 100 years. The paper aims to (i) describe observed trends and scenarios for summer heat waves, windstorms and heavy precipitation, based on results from simulations with global circulation models, regional climate models, and other downscaling procedures, and (ii) discuss potential impacts on agricultural systems and forests in Switzerland. Trends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(93 citation statements)
references
References 93 publications
2
91
0
Order By: Relevance
“…As a consequence of all these potential impacts of climate change on the health of plants and their associated organisms, there is increasing recognition that we need to develop strategies for long-term adaptation and insurance in agriculture and silviculture (Fuhrer et al 2006;Ciscar et al 2011). The importance of adaptive management is also stressed from the point of view of North American forest management by Millar et al (2007), who point out that future climate change challenges will not be met by a single solution, but by a mix of different approaches adapted to different situations.…”
Section: Plant Health Management Strategies: Diversity Is Neededmentioning
confidence: 99%
“…As a consequence of all these potential impacts of climate change on the health of plants and their associated organisms, there is increasing recognition that we need to develop strategies for long-term adaptation and insurance in agriculture and silviculture (Fuhrer et al 2006;Ciscar et al 2011). The importance of adaptive management is also stressed from the point of view of North American forest management by Millar et al (2007), who point out that future climate change challenges will not be met by a single solution, but by a mix of different approaches adapted to different situations.…”
Section: Plant Health Management Strategies: Diversity Is Neededmentioning
confidence: 99%
“…Moreover, various authors concluded that a high kinetic energy is a common indicator of a high rainfall erosivitiy and indeed more gully erosion. Salako (2008) and Fuhrer et al (2006) opined that climate variability is an important factor to determine rainfall erosivity as there is a decrease in rainfall where rainfall erosivity is considered to be high. Also, climate change affects the intensity, amount, frequency and type of rainfall in the United Kingdom thereby affecting the soil erodibility rate.…”
Section: Resultsmentioning
confidence: 99%
“…The 2003 drought event had severe impacts on both the environment (e.g. significantly lower discharge in many rivers; rapid mass losses of mountain glaciers; unusually high amounts of slope instability events) and on socio-economic systems (heat-related health problems and mortality, economic losses for the agricultural and the energy sector) (BUWAL et al, 2004;ProClim, 2005;Fuhrer et al, 2006;Beniston, 2007). Public authorities, politicians and the different water users, such as farmers, shipping operators, hydropower companies, health services and forest fire services, were surprised by the severity of the drought event and by its impacts.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%